Zircon U–Pb dating constraints on the crustal melting event around 8 Ma in the eastern Himalayan syntaxis. Issue 1 (2nd January 2016) - Tu, Ji-Yao; Ji, Jian-Qing; Gong, Jun-Feng; Yan, Quan-Ren; Han, Bao-Fu
Abstract: We determined detailed U–Pb ages for zircons in migmatitic granites densely exposed in the Namche Barwa peak (NBP) area, the core area of the eastern Himalayan syntaxis (EHS). The cores of these zircons show ages ranging from 863 to 1, 256 Ma, with high Th/U ratios. These ages correspond to the crystallization age of the Proterozoic Indian continental basement. The majority of zircon rims from these migmatitic granites yield a significant age peak at about 8 Ma with an increase in Th/U ratios, suggesting that a large-scale partial crustal melting event occurred at 8 Ma in the NBP area. Because thermochronologic results have demonstrated that a rapid denudation started around 8 Ma, we interpret this large-scale partial melting of the crust as a decompression melting caused by rapid denudation in the NBP area. The rapid denudation at 8 Ma probably resulted from the combination of tectonic activities and surface erosion.